Cytotoxic Effect of the Locally Isolate Lactococcus lactis Cell Wall Proteins on Tumor Cell Lines - Al-Shaibani, Moyassar B H; Al-Shekhly, Ali Abbdul-Rahman T; Abdul-Majeed, Mohammad R (Al-Nahrain Journal of Science, 2018)
This project was conducted to study the activity of cell wall components present in one of a human microflora which is Lactococcus lactis on AMN-3 and Hep-2 tumor cell lines in vitro. Twenty samples of dairy products (bucolic sour yoghurts, pasteurized milk and raw milk) were collected; nine isolates of Lactococccus were isolated by propagating in MRS broth medium followed by subjecting the isolates to microscopic, cultural, physiological and biochemical tests. The isolates were grown in M17 broth medium, at 37ºC for 6 hrs followed by extraction cell wall proteins using sonication method followed by estimation the concentrations of extracted proteins depending on standard curve of bovine serum albumin. The cytotoxic activity of different concentrations was studied on AMN-3 and Hep-2 tumor cell lines for three incubation periods (24, 48 and 72 hrs) in addition to normal rabbit embryo fibroblast (REF) cell line for 72 hrs only. The results showed the presence of four isolates belong to the genus Lactococcus lactis. The result showed a clear cytotoxic activity of these crude extracts with high significances on these tumor cell lines during the three incubation periods, suggesting that the cytotoxic effect of CWP is a dose and time dependent, but on REF cell line, there is no significant effect reported. It is concluded that CWP of L. lactis may possess some specificity in cytotoxicity on cancer cells but not on normal cells.